Studies on Depuration of Uve lams (Villorita sp.) - BALACHANDRAN, K K; SURENDRAN, P K (Fishery Technology, 2017)
Live clams collected from their natural beds were depurated by starving them in water. Water from their natural environment, potable water from municipal water supply and sodium chloride solution made up to the strength of natural brackishwater as well as all these chlorinated at 5 p.p.m level were used. The acid insoluble ash could be brought down to insignificant level by depuration in natural water for a period of16-18 h. Bacterial quality of the meat also could be improved by this method. Chlorination of the system at the end of depuration further improves the bactetial quality of the meat.